The unsteady aerodynamic forces on deforming, low aspect ratio wings and slender wing-body combinations oscillating harmonically in a compressible flow - Milne, R. D. (College of Aeronautics, Cranfield, 1955)
A method is presented whereby the 'Slender Body Theory' can be applied to the determination of the unsteady aerodynamic forces acting on slender wings and wing-body combinations experiencing harmonic deformations in a compressible flow. The analysis holds for subsonic and supersonic speeds, subject to restrictions which are stated and discussed.